Microbial mineralization of pyrogenic organic matter in different mineral systems. (August 2016) - Woo, Seung H.; Enders, Akio; Lehmann, Johannes
Highlights: Charring decreased mineralization to a greater extent than differences in minerals. Mineralogy less important for mineralization than organic matter properties. Mineralogy less important for mineralization of charred than uncharred organic matter. Abstract: The objectives of the study were to (i) investigate whether short term mineralization varies to a greater extent by charring organic matter (OM) or by exposure to different mineral surfaces, (ii) examine the effect of clay mineralogy on mineralization of either charred or uncharred OM and (iii) quantify these differences in mineralization in the context of C evolution during charring. Mineralization of different combinations of OM types (corn stover, cellulose, glucose, lignin and arginine) or their corresponding pyrogenic organic matter (PyOM) with minerals (quartz, corundum, goethite, kaolinite and kaolinite mixed with goethite) were assessed in incubation experiments at 30 °C for 196 days. All PyOM materials showed lower mineralization extent (3.8–7.5% of initial C) than uncharred OM (7.6–89% of initial C). Charring decreased mineralization to a greater extent (by 4.7–95%) than differences in the minerals (by 3.7–70%). The relative standard deviation of C mineralization of individual charred OM materials caused by differences in mineralogy was smaller (8.7–16%) than that of uncharred OM (8.7–65%). For the ratio of C remaining after both mineralization and charring to mineralization of uncharred biomass, the relative standard deviation was higher for different OM types (51–84%) than mineral types (1.1–47%), suggesting that mineralogy was less important than OM properties. Therefore, the importance of mineralogy was lower for charred than uncharred OM and the type of PyOM more strongly controlled mineralization than the type of mineral during the initial decomposition process.